New Species of Aprostocetus (Hymenoptera: Eulophidae) Associated with Pit Galls on Terminalia arjuna Leaves from Uttarakhand, India - Kumar, Vishal; Kumar, Sandeep (Journal of the Bombay Natural History Society (JBNHS), 2020)
A new species of the genus Aprostocetus Westwood (Hymenoptera: Eulophidae), described as Aprostocetus arjuna sp. nov., was collected from Khatima, Udham Singh Nagar, India. This new species was found to be associated with pit galls on the leaves of Terminalia arjuna tree.